If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = 2x + -5x * 3 Reorder the terms for easier multiplication: x = 2x + -5 * 3x Multiply -5 * 3 x = 2x + -15x Combine like terms: 2x + -15x = -13x x = -13x Solving x = -13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13x' to each side of the equation. x + 13x = -13x + 13x Combine like terms: x + 13x = 14x 14x = -13x + 13x Combine like terms: -13x + 13x = 0 14x = 0 Divide each side by '14'. x = 0 Simplifying x = 0
| x-(-2)=-23 | | 3a+2+4+6= | | 14=10y | | 9.75=3.9-1.5x | | x+(-33)=-3 | | -4x(x+6)+165=5x-9(x-9) | | (2x+8)+6=-3 | | 3(2x+5)=7 | | 4(3x+5)=5x-(10+3x) | | x-47=-13 | | -5=-3x+35 | | -45+x=23 | | 5(2x+4)=x+3(3x+6)+2 | | 2x^2+15x-5.9=0 | | x-(-5)=-71 | | 10x^2+54=0 | | x-142=-68 | | x+y-xz=x | | 8x-92=4x-8 | | x+4+3x=0 | | 3+35x=28x+29 | | y-x(1+z)=x | | .60x=30 | | (x+3)(2x-12)=0 | | p(x)=2x+-1 | | 0=2x^2+8x-960 | | 18=500x-5x^2 | | 11x+y=-27 | | -4x+6=0-5x | | 8n=51+3 | | 3x+10=-22-5 | | 270=(13+2x)x(9+2x) |